Raman scattering of graphene‐based systems in high magnetic fields. (1st August 2017) - Faugeras, Clement; Orlita, Milan; Potemski, Marek
Abstract : We review the different results obtained in the last decade in the field of Raman scattering of graphene‐based systems, with an applied magnetic field. Electronic properties of graphene‐based systems with an applied magnetic field are first described. The phonon response in magnetic field, the magneto‐phono resonance, is then introduced and described for graphene monolayer and multilayer, as well as for bulk graphite. Electronic Raman scattering are then discussed in the context of Landau level spectroscopy, of electron–phonon interaction and of electron–electron interaction. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We review in this article the different results obtained in the last decade in the field of Raman scattering of graphene‐based systems, with an applied magnetic field. Such techniques allow addressing the physics of electron–phonon and electron–electron interactions in graphene monolayer and multilayer, as well as in bulk graphite.